2017
DOI: 10.1002/mnfr.201600952
|View full text |Cite
|
Sign up to set email alerts
|

Jaboticaba berry peel intake prevents insulin‐resistance‐induced tau phosphorylation in mice

Abstract: The hyperphosphorylation of microtubule-associated protein tau (tau) in the hippocampus can be caused by central and peripheral insulin resistance and these alterations are related to the development of tauopathies, such as Alzheimer's disease. In this study, we used a high-fat diet to induce obesity and insulin resistance in adult Swiss mice and checked whether supplementation with Myrciaria jaboticaba berry peel for 10 weeks could improve insulin sensitivity, learning/memory performance, and prevent tau phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
(70 reference statements)
3
20
0
Order By: Relevance
“…A previous study has characterized the aqueous extract of jaboticaba peel (da Silva et al, ), showing that aqueous extraction is able to remove polyphenols from the peel, mainly anthocyanin, resulting in a demonstrably strong antioxidant capacity. This extraction method could be easily applied to in vivo use since benefits of the jaboticaba peel have already been shown, such as positive effects on antioxidant defense, glycemic response, and lipid levels (Batista et al, ; Batista, Leite‐Legatti, De Lima, Prado, & Maróstica Junior, ; Plaza et al, ). In this sense, this study confirmed the efficacy of aqueous extraction, using in vitro tests as a means of obtaining bioactive compounds from jaboticaba ( P. jaboticaba) peel in order to evaluate the in vivo effects of the extract on anti‐radical defenses and gut microbiota in healthy rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has characterized the aqueous extract of jaboticaba peel (da Silva et al, ), showing that aqueous extraction is able to remove polyphenols from the peel, mainly anthocyanin, resulting in a demonstrably strong antioxidant capacity. This extraction method could be easily applied to in vivo use since benefits of the jaboticaba peel have already been shown, such as positive effects on antioxidant defense, glycemic response, and lipid levels (Batista et al, ; Batista, Leite‐Legatti, De Lima, Prado, & Maróstica Junior, ; Plaza et al, ). In this sense, this study confirmed the efficacy of aqueous extraction, using in vitro tests as a means of obtaining bioactive compounds from jaboticaba ( P. jaboticaba) peel in order to evaluate the in vivo effects of the extract on anti‐radical defenses and gut microbiota in healthy rats.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the potential of jaboticaba peel extract to ameliorate some consequences of diet‐induced obesity is evident in the fact that it increases acetate production (Lenquiste et al, ). Previous studies have already attributed the prevention of weight gain and insulin sensitivity to the intake of raw jaboticaba peel, added to diets in obesity models (Batista et al, ; Lenquiste et al, ). This is another aspect that could be further explored in studies with the JAE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results suggest that anthocyanins reduce the extent to which ROS facilitate the functioning of the PI3K/AKT pathway and, therefore, have a neuroprotection effect by preventing apoptosis. Moreover, ingestion of Myrciaria jaboticaba berry peel berry peel minimizes GSK3β-mediated tau phosphorylation in the hippocampus of 3-week-old weaned male Swiss mice, corroborating better learning/memory performance [ 243 ]. The antioxidant effect of anthocyanins in the brain is also confirmed in animal studies through oxidative biomarkers levels.…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 87%
“…This enhancement is confirmed by Western blot analysis of the memory-associated presynaptic and postsynaptic protein markers [ 239 , 240 ] and by behavioral tests. Anthocyanins improve learning and memory, which has been confirmed by the Morris water maze [ 240 , 243 , 244 , 245 , 252 , 253 , 254 , 260 , 264 , 265 , 266 ], Y-maze [ 240 , 255 ], novel object recognition [ 241 , 248 , 260 , 265 ] and passive avoidance [ 245 , 254 , 263 ] tests. Motor coordination is also improved by anthocyanins as confirmed by rotating rod test [ 244 ] and open-field [ 248 , 263 ] tests.…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 90%